Factors Associated with Pulmonary Function Changes in Patients Undergoing Microwave Ablation for Pulmonary Ground-Glass Nodules - Weida Wu MD; Jianyang Peng BD; Hongbin Gao MD; Yuanzhen Lin MD; Qunying Lin BD; Zhicheng Weng MD (Technology in Cancer Research & Treatment, 2022)
Purpose: Microwave ablation has become an alternative treatment for pulmonary ground-glass nodules (GGN) and is widely accepted by clinicians. However, its effect on lung function remains unknown. Therefore, this retrospective study aimed to explore pulmonary function changes and associated risk factors in patients undergoing computed tomography (CT)-guided microwave ablation (MWA) for treating pulmonary GGN. Materials and Methods: Thirty-five patients diagnosed with pulmonary GGN on thin-layer chest CT and enhanced CT were examined. Patients unable or unwilling to undergo thoracoscopic surgery underwent CT-guided simultaneous percutaneous core needle biopsy and MWA. Pulmonary function tests (PFT) were performed before ablation and 3 days and 6 months post-ablation. Forced expiratory volume in one second (FEV1), FEV1%, forced vital capacity (FVC), maximal voluntary ventilation (MVV), and peak expiratory flow (PEF) values pre- and post-MWA were analysed. Linear regression analysis was used to examine the correlation between ablation volume and changes in PFT findings 3 days post-ablation. Associations between patient characteristics, rates of postoperative complications, and PFT findings were analysed. Results: Forty-eight lesions were completely ablated and examined intraoperatively. There were significant differences in pre- and post-operative PFT findings on day 3 but not at 6 months. The mean ablation volume after 3 days of 11.4 ± 6.3 cm 3 was positively correlated with changes in FEV1, MVV, and PEF values. Patients’ age (mean, 59.4 ± 13.0 years) positively correlated with changes in PEF values. The rates of change in FVC and MVV values were significantly higher with multiple pulmonary nodules than with isolated pulmonary nodule. PFT findings were similar between patients who experienced or did not experience complications (eg, pneumothorax and pleural effusion). Conclusions: Pulmonary function could be impaired shortly after MWA. PFT findings may correlate with age, ablation volume, and number of ablated lesions. In most patients, pulmonary function returned to the preoperative state after 6 months.